3D Android game Hide-n-Seek - Tilotkar, Sanket; Makwana, Mehul; Sayyed, Siraj; Naikbawane, Aditya (International Journal of Computer Sciences and Engineering, 2025)
The project is about 3D game development based on android operating system. 3D game development is an exciting activity for many student. The game is all about “3D Hide N Seek”.The purpose of this project is to provide students with entertainment and fun. The goal of our project is to develop a game with 3D graphics with good performance. An essential objective is its a “multi-player” feature. Player can connect via bluetooth. The other feature is “leaders board” over the globe playing this 3D game using Database SQL lite. 3D game is being developed using unity 3 software as it required graphics. Graphics using openGL es or photo shop for clean and realistic objects. The game is all bout there will be a diner and other 4 player will hide (as max. 5 players can play at a time).the diner will find all the other players in minimum time as possible. There will be different areas like school, garden , etc. player can select area of his/her choice. Minimum time required to find all players will be player's(diner) high score(only in single player mode where 4 other players will be bots).